2019
DOI: 10.9734/jesbs/2019/v29i130100
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Characteristics, Training Attitudes and Well-being of Students: A Longitudinal Study

Abstract: Background: The first aim of this study was to investigate the influence of psychosocial characteristics on four training attitudes (motivation to learn, learning, transfer intention and cognitive dissonance) and well-being. The second — and main — aim was to examine the impact of attitudes to training on individual levels of well-being. Methodology: This study used a longitudinal approach comprising two phases of data collection. One-hundred and eighty first-year psychology students participated in Phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 86 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Master students have pre-established (functional) social support networks within the university and know how/when to access the necessary social resources required to perform academically (Cilliers and Flotman 2016 ). These students are also known to present with higher levels of academic self-efficacy and may have crystalised coping mechanisms to manage both study-related- and environmental demands (Jorgensen et al 2016 ; Nor and Smith 2019 ). Master students may therefore be less susceptible to the impact of the lockdown procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Master students have pre-established (functional) social support networks within the university and know how/when to access the necessary social resources required to perform academically (Cilliers and Flotman 2016 ). These students are also known to present with higher levels of academic self-efficacy and may have crystalised coping mechanisms to manage both study-related- and environmental demands (Jorgensen et al 2016 ; Nor and Smith 2019 ). Master students may therefore be less susceptible to the impact of the lockdown procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the accumulated research on Benet-Martínez and Haritatos’s (2005) construct of BII, on which lower scores reflect a conflictual bicultural identity. Benet-Martínez et al (2006) showed among Chinese Americans that lower BII was related to more cognitive dissonance, which relates to poorer well-being (Nor & Smith, 2019). Examining BII of Italian transracial adoptees, who experience biculturalism in comparable ways to immigrants, Manzi et al (2014) indicated that lower BII predicted more behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on wellbeing has considered it as a process and measured it using the Wellbeing Process Questionnaire (WPQ - Williams & Smith 2012, 2016 or the Smith Wellbeing Questionnaire (SWELL - , 2017cFan & Smith 2017a, 2018. Versions of these questionnaires have been developed for research with students (Williams, Pendlebury, Thomas & Smith, 2017;Alharbi & Smith, 2019;Nor & Smith, 2019) and a key feature of these measures has been that they consist of short scales which have been shown to be correlated with longer established measuring instruments. These short questionnaires have been shown to have good reliability and validity.…”
Section: Introductionmentioning
confidence: 99%